Novel fit formula for the calculation of hysteresis losses including DC-premagnetization - Stenglein, Erika; Kübrich, Daniel; Albach, Manfred; Dürbaum, Thomas (PCIM Europe Conference Proceedings, 2019)
In the field of power electronics, optimizing inductive components achieves objectives such as increased efficiency, cost savings and/or miniaturization. However, core loss prediction for arbitrary excitations is quite complex and no comprehensive approach has been developed so far. In particular, the influence of DC-premagnetization cannot be neglected. This paper adopts the volt-amperometric-method to measure hysteresis loss for different excitations and DC-premagnetizations in the magnetic flux density. Moreover, the dependence of hysteresis loss on magnetic history is investigated, an issue that is usually not addressed in literature. Finally, this paper provides a novel easy-to-handle formula to estimate hysteresis loss including DC-premagnetization.
CRIS-Team Scopus Importer:2021-04-20